4x-7x-14=-3x+3-14

Simple and best practice solution for 4x-7x-14=-3x+3-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-7x-14=-3x+3-14 equation:


Simplifying
4x + -7x + -14 = -3x + 3 + -14

Reorder the terms:
-14 + 4x + -7x = -3x + 3 + -14

Combine like terms: 4x + -7x = -3x
-14 + -3x = -3x + 3 + -14

Reorder the terms:
-14 + -3x = 3 + -14 + -3x

Combine like terms: 3 + -14 = -11
-14 + -3x = -11 + -3x

Add '3x' to each side of the equation.
-14 + -3x + 3x = -11 + -3x + 3x

Combine like terms: -3x + 3x = 0
-14 + 0 = -11 + -3x + 3x
-14 = -11 + -3x + 3x

Combine like terms: -3x + 3x = 0
-14 = -11 + 0
-14 = -11

Solving
-14 = -11

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| p+p+49+p+49=144 | | p+p+49+(p+49)=144 | | x+5+3x-1=7.6 | | 3(4k+14)=10k-2k(k-7) | | 6x=-p/3-2p | | 0.18(y-1)+0.20y=0.02y-0.09(40) | | 2*x-1=15 | | 9-(3n-4)=7-4n | | 53=25+250m | | ((2x^4)/7)-((9x^2)/14) | | 156+65h=351 | | 9m+14m+10=-5 | | 7.20h=57.60 | | 4(x-7)+2(2x+6)=7(x-3)+7 | | -5.1-(-1.4)=x | | 2x+2+-3=5x+8 | | 4+11=x+2 | | I=8A/(T+B) | | -7n+11=5n-17 | | l+2l+(l+7)=115 | | .60b=.72 | | -8b-6(b-7)=-2b-2(2b+7) | | 1/2*5.4(7+5) | | I=8A/T+B | | 0.49/0.04=x | | x^2+(x+3)*(x+3)=89 | | 3y-8x=21 | | 14x(6+16)--27=41 | | 36-2n=72 | | 3x-(4)=14 | | 12h=9h+-9h | | (1/4)(x+2)^2-9 |

Equations solver categories